Work absenteeism due to a chronic disease - Guy Lacroix; Marie-Ève Brouard (Institute for the Study of Labor (IZA), 2011)
Research on health-related work absenteeism focuses primarily on moral hazard issues but seldom discriminates between the types of illnesses that prompt workers to stay home or seek care. This paper focuses on chronic migraine, a common and acute illness that can prove to be relatively debilitating. Our analysis is based upon the absenteeism of workers employed in a large Fortune-100 manufacturing firm in the United States. We model their daily transitions between work and absence spells between January 1996 up until December 1998. Only absences due to migraine and depression, its main comorbidity, are taken into account. Our results show that there is considerable correlation between the different states we consider. In addition, workers who are covered by the Blue Preferred Provided Organization tend to have shorter employment spells but also shorter migraine spells.
urn:nbn:de:101:1-201104133822
Keywords: I10; J32; 330; migraine; absenteeism; insurance policies; transition models; unobserved heterogeneity; Erwerbsunfähigkeit; Fehlzeit; Chronische Krankheit; Krankenversicherung; USA